Linkage to nodal osteoarthritis: quantitative and qualitative analyses of data from a whole-genome screen identify trait-dependent susceptibility loci. Issue 9 (27th February 2006) - Greig, C; Spreckley, K; Aspinwall, R; Gillaspy, E; Grant, M; Ollier, W; John, S; Doherty, M; Wallis, G
Abstract : Objective: To identify susceptibility loci for nodal osteoarthritis. Methods: A genome screen at an average marker spacing of 9.29 cM was carried out on 558 people from 202 families, of whom 491 had nodal osteoarthritis. All genotyped people were graded for the incidence and severity of distal interphalangeal (DIP) nodes, and radiographs from 354 people were graded for joint-space narrowing (JSN) and osteophytes (OSTs). Age-regressed indices for DIP nodes, JSN and OSTs were calculated using these phenotypic data. Affected sibling pair (ASP) and quantitative trait analyses were carried out using MERLIN. Results: The data analysis identified suggestive linkage to loci on chromosomes 3 (for JSN and OST), 4 (for JSN), 8 (for DIP), 11 (for radiographic osteoarthritis) and 16 (for JSN). Both the ASP and quantitative analyses identified the loci on chromosomes 4 and 11. The loci on chromosomes 3 and 16 overlap with those previously identified for large-joint osteoarthritis. Of the loci identified by the quantitative analyses with the logarithm of the odds of linkage >1.5, two were linked to more than one trait, whereas nine were linked to single traits: one for DIP, six for JSN and two for OST. Conclusion: The ASP and quantitative analyses of the cohort with nodal osteoarthritis suggest that multiple susceptibility loci for osteoarthritis influence the traits, which combine to form the osteoarthritis phenotype, and that these loci may not act exclusively on the joints of the hand.